Pengaruh Minat Belajar dan Kedisiplinan terhadap Kemampuan Berhitung Pembagian pada Siswa Kelas V di SD Muhammadiyah 24 Surakarta Tahun Pelajaran 2015/2016 - Prasetyo, Rochmat Tony, Drs. Suwarno, S.H, M.Pd (2016)
Education has a strategic role in improving human resources and the realization of the ideals of the Indonesian nation in realizing common prosperity and intellectual life of the nation. The purpose of this study was to determine include: 1) Effect of interest in learning against the division numeracy skills in class V in SD Muhammadiyah 24 Surakarta academic year 2015/2016, 2) Effect of discipline against the division numeracy skills in class V in SD Muhammadiyah Surakarta 24 academic year 2015/2016, 3) Effect of learning and discipline against the division numeracy skills in class V in SD Muhammadiyah 24 Surakarta academic year 2015/2016. This study uses a quantitative approach to this type of research Ex-Post Facto. The analysis technique used is multiple regression, t test, and Test F. Based on the analysis of data: 1) The equation of the regression coefficients obtained Y = 31,325+ 0,111X1 + 0.067 X2. 2) Test Results Interest in Learning thitung t (4.295)> t table (2.037), interest in learning positive influence on students' numeracy skills sharing. 3) Discipline positive effect on the distribution of students' numeracy skills, it is based on t test results tcount (3.204)> t table (2.037). 4) Test Results f significance value 0.000 <0.05; means interest in learning and discipline together positive effect on numeracy division of fifth grade students at SD Muhammadiyah 24 Surakarta academic year 2015/2016.